Broadly neutralizing antibodies isolated from HEV convalescents confer protective effects in human liver-chimeric mice - Ssebyatika, George; Dinkelborg, Katja; Ströh, Luisa J.; Hinte, Florian; Corneillie, Laura; Hueffner, Lucas; Guzman, Elina M.; Nankya, Prossie L.; Plückebaum, Nina; Fehlau, Lukas; Garn, Jonathan; Meyer, Nele; et al. (Nature Communications, 2025)
Hepatitis E virus (HEV) causes 3.3 million symptomatic cases and 44,000 deaths per year. Chronic infections can arise in immunocompromised individuals, and pregnant women may suffer from fulminant disease as a consequence of HEV infection. Despite these important implications for public health, no specific antiviral treatment has been approved to date. Here, we report combined functional, biochemical, and X-ray crystallographic studies that characterize the human antibody response in convalescent HEV patients. We identified a class of potent and broadly neutralizing human antibodies (bnAbs), targeting a quaternary epitope located at the tip of the HEV capsid protein pORF2 that contains an N-glycosylation motif and is conserved across members of the Hepeviridae. These glycan-sensitive bnAbs specifically recognize the non-glycosylated pORF2 present in infectious particles but not the secreted glycosylated form acting as antibody decoy. Our most potent bnAb protects human liver-chimeric mice from intraperitoneal HEV challenge and co-housing exposure. These results provide insights into the bnAb response to this important emerging pathogen and support the development of glycan-sensitive antibodies to combat HEV infection.
Gesehen am 31.07.2025